2022
DOI: 10.3390/biomedicines10071623
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Systemic Treatment of a Mouse Model Displaying Chronic FSHD-like Pathology with Antisense Therapeutics That Inhibit DUX4 Expression

Abstract: Silencing the expression of the double homeobox 4 (DUX4) gene offers great potential for the treatment of facioscapulohumeral muscular dystrophy (FSHD). Several research groups have recently reported promising results using systemic antisense therapy in a transgenic small animal model of FSHD, the ACTA1-MCM/FLExDUX4 mouse model. However, the treatment was applied in non-DUX4-induced mice or shortly after DUX4 activation, which resulted in conditions that do not correctly represent the situation in a clinic. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 52 publications
(117 reference statements)
1
12
0
Order By: Relevance
“…The effect of AAV8-MD1 delivery on muscle fibrosis was analyzed by assessing the expression of collagen VI, periostin, and fibronectin, all considered markers of fibrosis [23][24][25][26]. As shown in Figure 4A, the diaphragms of the Dba2/J control mice already showed a level of fibrosis, as has been reported previously for skeletal muscles of this mouse, but the diaphragms of the D2.mdx mice displayed more collagen VI deposition.…”
Section: Microdystrophin Gene Addition In D2mdx Mice Prevents Fibroti...supporting
confidence: 68%
See 1 more Smart Citation
“…The effect of AAV8-MD1 delivery on muscle fibrosis was analyzed by assessing the expression of collagen VI, periostin, and fibronectin, all considered markers of fibrosis [23][24][25][26]. As shown in Figure 4A, the diaphragms of the Dba2/J control mice already showed a level of fibrosis, as has been reported previously for skeletal muscles of this mouse, but the diaphragms of the D2.mdx mice displayed more collagen VI deposition.…”
Section: Microdystrophin Gene Addition In D2mdx Mice Prevents Fibroti...supporting
confidence: 68%
“…Histological analysis was performed following a protocol by Lu-Nguyen and colleagues [26]. Collagen VI immunostaining was used to determine the fibrotic area of each sample.…”
Section: Histological Analysismentioning
confidence: 99%
“…We also studied the number of centrally nucleated myofibers found in gastrocnemius muscles in DUX4-TG mice [ 11 , 15 , 17 , 18 , 29 ]. The nuclei of regenerated mouse myofibers stay central for several months [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…TMX injection causes transient symptoms with a 2-week peak, probably because dying DUX4-expressing muscle cells are compensated by regenerating non-DUX4-expressing muscle cells [ 10 ]. Lu-Nguyen et al [ 17 ] have demonstrated the chronic disease progression model, where DUX4-TG mice were repeatedly treated with 1.5 mg/kg of TMX every other week. However, they did not show how much the disease was exacerbated by such a low dose of TMX compared with TMX-untreated DUX4-TG mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation